Sulfate brines in fluid inclusions of hydrothermal veins: Compositional determinations in the system H2O-Na-Ca-Cl-SO4. (15th July 2017) - Walter, Benjamin F.; Steele-MacInnis, Matthew; Markl, Gregor
Abstract: Sulfate is among the most abundant ions in seawater and sulfate-bearing brines are common in sedimentary basins, among other environments. However, the properties of sulfate-bearing fluid inclusions during microthermometry are as yet poorly constrained, restricting the interpretation of fluid-inclusion compositions where sulfate is a major ion. The Schwarzwald mining district on the eastern shoulder of the Upper Rhinegraben rift is an example of a geologic system characterized by sulfate-bearing brines, and constraints on the anion abundances (chloride versus sulfate) would be desirable as a potential means to differentiate fluid sources in hydrothermal veins in these regions. Here, we use the Pitzer-type formalism to calculate equilibrium conditions along the vapor-saturated liquidus of the system H2 O-Na-Ca-Cl-SO4, and construct phase diagrams displaying the predicted phase equilibria. We combine these predicted phase relations with microthermometric and crush-leach analyses of fluid inclusions from veins in the Schwarzwald and Upper Rhinegraben, to estimate the compositions of these brines in terms of bulk salinity as well as cation and anion loads (sodium versus calcium, and chloride versus sulfate). These data indicate systematic differences in fluid compositions recorded by fluid inclusions, and demonstrate the application of detailed low-temperature microthermometry to determine compositions of sulfate-bearing brines. Thus, these data provide new constraints on fluid sources and paleo-hydrology of these classic basin-hosted ore-forming systems. Moreover, the phase diagrams presented herein can be applied directly to compositional determinations in other systems.